Identification of protozoa in the rumen of indonesian indigenous cattle - Rizka Muizzu Aprilia; Hendrawan Soetanto (Faculty of Animal Science, Universitas Brawijaya, 2021)
Information on the dominant protozoa in local cattle, especially on Ongole Cross-bred, Bali, and Madura Cattle cattle, is still little disclosed in the article. This study aimed to provide information and characteristics of the dominant protozoa in the rumen of local cattle. The material used in the form of digesta and rumen fluid collected from abatoar Pegirian, Surabaya city, East Java. The method used is observation under an electron microscope (10 x 10) using a Sedgewick Rafter counting chamber S52. The results showed that the basal feed given in the form of forage was indicated by the NDF and ADF digesta values. The feed is very closely related to the presence of the dominant genus of protozoa. The dominant genus of OCB and Bali Cattle is Eudiplodinium, while in Madura cattle, it is the genus Entodinium